2022
DOI: 10.2166/wst.2022.121
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of levofloxacin on natural zeolite: effects of ammonia nitrogen and humic acid

Abstract: The persistence of antibiotics in sewage treatment plants in recent years has become a serious problem. Meanwhile, humic acid and ammonia nitrogen are widely distributed in natural reservoirs and might influence the sorption, migration and transformation of antibiotics. In this study, natural zeolite (NZ) was evaluated as an adsorbent for the removal of levofloxacin (LEV). The physical and chemical properties of NZ before and after adsorption were characterized by various analytical techniques to develop the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The uptake capacity of Ch-W composite increased from 1.89 mg g −1 to 7.42 mg g −1 as the concentration was increased from 1 to 10 mg L −1 . Similar behavior was reported by Chi et al (2022) where the uptake capacity of natural zeolite reached ~ 20 mg g −1 at 20 mg L −1 . Al-Jabari et al ( 2019) stated that the highest levofloxacin removal using chemical Fe 3 O 4 nanoparticles was at pH 6.5, and the contact time was 240 min.…”
Section: The Initial Concentration Effectsupporting
confidence: 88%
See 1 more Smart Citation
“…The uptake capacity of Ch-W composite increased from 1.89 mg g −1 to 7.42 mg g −1 as the concentration was increased from 1 to 10 mg L −1 . Similar behavior was reported by Chi et al (2022) where the uptake capacity of natural zeolite reached ~ 20 mg g −1 at 20 mg L −1 . Al-Jabari et al ( 2019) stated that the highest levofloxacin removal using chemical Fe 3 O 4 nanoparticles was at pH 6.5, and the contact time was 240 min.…”
Section: The Initial Concentration Effectsupporting
confidence: 88%
“…Antibiotics are not completely digested by the body, and approximately 80% of antibiotics are excreted as unmetabolized compounds in their parent forms (Chi et al 2022). Until now, municipal wastewater treatment plants have not had the potential to completely remove PPCPs and can reach the environmental compartments (Gwenzi et al 2022;Cao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Various ester prodrugs of LFX including LFX-EHE prevented chelate formation possibly by steric hindrance of the binding site in vitro and in vivo [ 31 , 32 , 33 , 74 ]. In addition to chelate formation in water, quinolones also interact with cationic metal-containing solid materials by physicochemical adsorption [ 15 , 29 , 75 , 76 , 77 ]. For example, the reported rate of adsorption of several quinolones (50 µM) onto solid Al(OH) 3 (2.5 mg/mL) was in the following order: norfloxacin (NFX, 72.0%) > enoxacin (ENX, 61.0%) > LFX (48.1%) = OFX, (47.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The significant heterogeneity and structural complexity of HAs, attributed to diverse sources and ecological systems, pose challenges to research on HAs [34]. Studies have demonstrated the fundamental importance of isolating and purifying HAs for their characterization and utilization.…”
Section: Ha Fractionation 221 Methods Of Ha Fractionationmentioning
confidence: 99%